Meningkatkan Eksistensi Agroindustri Temerodok melalui Pengembangan Varian Sebagai Wujud Ekonomi Kreatif di Desa Sakra - Roy Setiadi; Aminah Aminah; Baiq Sari Supriantini; Lalu Randa Hazri Ramdani; Siti Soleha; Hamidsyukrie Hamidsyukrie; Syahrial Ayub; Muhammad Taufik; Syafruddin Syafruddin; Saprizal Hadisaputra (Pascasarjana Universitas Mataram, 2021)
This community service aims to improve the existence of the Temerodok Agroindustry through the development of new flavors as a form of creative economy in Sakra Village, East Lombok Regency. This community service is carried out for 45 days and is trained and produced twice a week. The method of making Temerodok is still a simple technique by not preserving the local wisdom. This Temerodok product, having expanded its existence and developed variants, is recognized by the wider community and not just the people of Sakra Village. The developed variant is also very popular with the wider community, especially in all circles. In terms of packaging, use a paper bag so that it is environmentally friendly and looks attractive and can be one of the local specialties. The establishment of this company is part of the development process to improve the existence of Temerodok's agro industry